2016
DOI: 10.4209/aaqr.2015.05.0323
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide in the Free Troposphere and Boundary Layer at the Mt. Bachelor Observatory

Abstract: We use data for 2012-2014 from the Mt. Bachelor Observatory (MBO) in central Oregon to understand variations in carbon dioxide (CO 2 ) in the free troposphere (FT) and boundary layer (BL). The goals of this analysis are to identify and examine CO 2 in FT and BL air, events due to wildfires, the role of transport patterns, and the variation of CO 2 seasonally. For all seasons, we found that FT air has higher average CO 2 mixing ratios compared to BL air. FT air was most often seen during the night and early mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The average water vapor for all categories is relatively high, which is indicative of boundary layer transport. This is common for midday at MBO (McClure et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…The average water vapor for all categories is relatively high, which is indicative of boundary layer transport. This is common for midday at MBO (McClure et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…The reference species Y has most commonly been carbon monoxide (CO) or carbon dioxide (CO 2 ), which are thought of as conserved, inert products of combustion (Andreae and Merlet, 2001;Hobbs et al, 2003). McClure et al (2016) showed that this is not always the case for CO 2 . Vegetation uptake can deplete CO 2 in WF plumes within the boundary layer, distorting the NER.…”
Section: Introductionmentioning
confidence: 99%
“…Bachelor Observatory (MBO) is located on a mountain top in central Oregon at 2.76 km above sea level. The observatory has been in operation for the last decade and has been previously used to study long-range transport and wildfire plumes (e.g., Jaffe et al, 2005;Fischer et al, 2011;Wigder et al, 2013;Baylon et al, 2015;McClure et al, 2016). In this study, we analyze wildfire plumes aged 1-2 days that were observed at MBO in 2012 and 2013.…”
Section: Introductionmentioning
confidence: 99%